The impact after 50 years of a new medical education programme with a regional workforce mission. (5th July 2017) - Hays, Richard; Bowles, Sarah; Brown, Terry; Lawler, Anthony; Vickers, James
Abstract: Background: Tasmania established its medical programme in 1965 to produce graduates to address medical workforce recruitment challenges. Many Tasmanian graduates work in Tasmania, but workforce problems continue. This paper reports the workforce outcomes of the first 42 graduating cohorts. Methods: A database for all University of Tasmania medical graduates from the years 1970 to 2011 was developed by combining information from university, registration and local workforce survey databases. Results: A total of 2012 doctors graduated from 1971 to 2011 and 1707 (85%) were registered, most commonly in general practice (45.8%), medicine (13%), anaesthetics (7.9%), surgery (7.5%), psychiatry (4.3%), emergency medicine (35, 3.5%), paediatrics (3.4%) and pathology (3.3%). While 41.9% worked in Tasmania, they comprised 35.6% of the local workforce and were clustered around the two larger cities. The proportion entering general practice has fallen since 1980s. Discussion: The contribution of the Tasmanian medical programme is substantial but appears less than other regional medical schools. Relatively few work in smaller communities, particularly in specialties other than general practice. Lifestyle choices and the availability of training opportunities and career positions might be contributing factors. The medical school has established clinical schools in rural communities, promoted admission of rural applicants and increased rural clinical placement opportunities, with some early signs of success. Conclusion: The Tasmanian medical programme is important in this regional, island economy, but the rural and remote communities have not benefited as much as the two larger cities. Sustaining a regional workforce mission over time might require frequent adjustments to admissions and curriculum processes.